Analisis Kebutuhan E-modul Siswa dengan Menggunakan Flipbook untuk Meningkatkan Kesadaran Sejarah Siswa di SMAN 1 Kinali pada Materi PDRI - Sartika, Dewi; Yefterson, Ridho Bayu (Jurnal Kronologi, 2026)
This study was motivated by the low level of historical awareness among Phase F.1 students at SMA Negeri 1 Kinali, as shown by the results of a prior knowledge test in which only about 40% of students answered correctly while 60% still experienced difficulties. Interviews with the history teacher indicated that digital learning resources had not been utilized, and the student needs survey confirmed the demand for alternative instructional materials. The limitations of printed textbooks, which are less visually engaging and do not discuss the topic of the Emergency Government of the Republic of Indonesia in depth, also contributed to this condition. This research aimed to develop a flipbook-based e-module as a supporting learning resource to improve students’ historical awareness. A mixed-method approach was employed using tests, interviews, and needs questionnaires. The findings indicate that an interactive digital module is needed to create more flexible, engaging, and meaningful learning, ultimately enhancing students’ historical awareness effectively and sustainably